Community-Based Livestock Breeding: Coordinated Action or Relational Process? - Wurzinger, Maria; Gutiérrez, Gustavo A.; Sölkner, Johann; Probst, Lorenz (Frontiers in Veterinary Science, 2021)
Over the past decade, community-based breeding programs (CBBP) have been promoted as a viable approach to improve smallholder livelihoods through systematic livestock breeding. CBBPs aim to initiate systematic breeding at the community level and build capacities and ownership among participants to ensure the programs' continuity. The study's purpose was to understand how CBBPs evolve in specific institutional settings and which dynamics occur at the project level. We addressed these questions in reflective conversations with six coordinators of CBBPs, using categories of the multi-level perspective to guide the interviews and the analysis. The respondents considered lack of funding and weak institutionalization, the main constraints slowing down the CBBPs. While the idea of participation and localized ownership was at the center of CBBPs, linear paradigms of knowledge transfer prevailed. In all cases, the impulse to start a CBBP came from individual researchers, who relied on intermediaries such as extension agents to implement the program. Personal relations and trust were seen as both a factor and a positive outcome of CBBPs. From the discussion of the findings, we conclude that the pathway to a successful CBBP depends on the perspective taken: from an innovation systems perspective, and aiming to scale up and out, concerted action and alignment of interests would be necessary. From the perspective of process-relational concepts, which question the continuity of institutions beyond daily interactions, CBBPs would need to become part of the researchers’ practice and engagement with the community.